Pattern of mobile phone usage among paddy farmers - Ramli, Nor Sabila; Man, Norsida; Hassan, Md. Salleh; Abu Samah, Bahaman; Omar, Siti Zobidah; Yusuf, Sarina; A. Rahman, Nur Atikah; Ibrahim, Muhamad Shamsul (Human Resource Management Academic Research Society, 2019)
One of the Information and Communication Technology (ICT) tools is a mobile phone. The mobile phone is unique in the most effective ways of reducing poverty in agriculture. It can invest and make improvements in the agriculture sector. To empower underprivileged farmers with information and communication belongings and facilities that will be increased their production and income as well as protect their food security and livelihood. Previous studies shows that ICT for development often debate that ICTs have the potential to aid in rural development and poverty reduction (Donner, 2006; Duncombe & Heeks, 2002; Hudson, 2004; Saunders et al., 1994). A quantitative study were applied to 400 paddy farmers in Integrated Agriculture Development Area (IADA). The ability of ICTs to bring refreshed momentum to agriculture appears even more convincing in light of growing investments in agricultural sector. This paper aims to explain the pattern of mobile phone usage among paddy farmers especially in Selangor area. This paper try to analyze descriptive to infer the result obtain. A good mobile phone usage pattern will effectively leverage ICT to develop agriculture.